2006
DOI: 10.1007/s11136-006-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

CDLQI, Scorad and Ness: Are they Correlated?

Abstract: Quality of life, disease severity scores and laboratory atopic markers represent different domains in AD assessment. They do not necessarily correlate well with each other and all three aspects must be individually evaluated to assess the well-being of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 24 publications
1
62
0
1
Order By: Relevance
“…Of all the severity scales used in atopic dermatitis, it is the most widely validated disease-severity instrument [9]. SCORAD has been found to be valid and reliable, and it has shown excellent agreement with global assessments of disease severity [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]. However, some studies have shown interobserver variation in scoring lichenification and extent of disease [8], [9], [10], [18], [20], [23].…”
Section: Resultsmentioning
confidence: 99%
“…Of all the severity scales used in atopic dermatitis, it is the most widely validated disease-severity instrument [9]. SCORAD has been found to be valid and reliable, and it has shown excellent agreement with global assessments of disease severity [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]. However, some studies have shown interobserver variation in scoring lichenification and extent of disease [8], [9], [10], [18], [20], [23].…”
Section: Resultsmentioning
confidence: 99%
“…These preliminary CDLQI results suggest that LS has a relatively small effect on a patient’s life quality 52 or that a LS-specific QOL tool may be needed. CDLQI correlated poorly with the mLoSSI, which measures different aspects of disease 53,54 .…”
Section: Discussionmentioning
confidence: 95%
“…Careful consideration of the scale properties should occur prior to use, including validity (content, construct, concurrent, discriminative), reliability (test-retest and internal consistency), responsiveness to change, and minimal clinically important difference. 58, 60, 67, 68 In clinical trials, the most commonly used scale is the Children’s Dermatology Life Quality Index (CDLQI), followed by the Dermatitis Family Impact (DFI), the Dermatology Life Quality Index (DLQI), and the Infant's Dermatology Life Quality Index. 43 But these scales were not generally designed for use in routine clinical practice.…”
Section: Disease Severity and Clinical Outcomes Assessmentmentioning
confidence: 99%